Pemodelan kapabilitas organisasi terhadap kinerja ditinjau dari faktor kepemimpinan-budaya organisasi-perilaku politik dalam organisasi- studi kasus pada kelompok perkebunan kelapa sawit negara dan kelompok perkebunan kelapa sawit swasta - Bangun, Yuni Ros; Mangkuprawira, Sjafri; Saefuddin, Asep; Djohar, Setiadi (SBM ITB, 2010)
Organizational Capability is considered to be one of the most important issues in strategic management and human capital literature. Organizational Capability can be understood as the all elements that work efficiently and effectively to help organization create its strategy that fits to its industry level of turbulence and to achieve company performance. Previous research confirmed the identification of nine (9) elements as organizational capability. These are speed innovation, customer connectivity, seeks related change, strategic responsiveness, international working environment, ready to strategic alliances, efficiency and talent. Research confirmed that Organizational Capabilities have positive impact to Organizational Performance. Research shows the connection between the three variables –Leadership –Organizational Culture and Political Behavior in creating Organizational Capability and its impact to Organizational Performance. Structural Equation modeling shows that Leadership and Organizational Culture do not have direct relationship with Organizational Performance, however both have positive relationship with Organizational Capability. Organizational Performance was directly influenced positively by Organizational Capability and negatively impacted by Organizational Politics. Leadership positively impact Organizational Capability and Organizational Culture, however leadership negatively impact Organizational Politics.Keywords: Strategic Management,Organizational Capability,Strategic Leadership, Culture,Organizatinal Politics,Government Owned Companies